2016
DOI: 10.2320/matertrans.m2016203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corrosion on Mechanical Reliability of Sn-Ag Flip-Chip Solder Joint

Abstract: The shear strength and failure behaviors of the Sn-2.3 mass%Ag ip-chip solder joints before and after corrosion test were investigated. The relationships between the shear strength, corrosion amount, and fracture mode are elucidated in this study. The shear strength of the Sn-Ag solder bump joints decreased with increasing amount of corrosion, mainly due to the formation of brittle corrosion products. In addition, the shear strength was changed with corrosion site. After the shear test, the failure mode switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It was reported that moisture induces mechanical stresses, hygroswelling [1], and local pressure variation, which cause delamination and fractures in the interconnections. Further studies have indicated corrosion phenomena [2], [3] and induced galvanic migration, which creates dendrites between the metal coating of the interconnections [4].…”
mentioning
confidence: 99%
“…It was reported that moisture induces mechanical stresses, hygroswelling [1], and local pressure variation, which cause delamination and fractures in the interconnections. Further studies have indicated corrosion phenomena [2], [3] and induced galvanic migration, which creates dendrites between the metal coating of the interconnections [4].…”
mentioning
confidence: 99%